Crédito rural: análise e proposições sobre o custeio agrícola no estado do Rio Grande do Sul - Gross, Daniel (2024)
The main tool of Brazilian agricultural policy is rural credit, which the government uses to promote the development of the sector and encourage the implementation of agendas considered important for the country, such as sustainability in production. In 2022, Rio Grande do Sul was the state that benefited most from this agricultural policy instrument, capturing 13.67% of the resources and issuing 15.15% of the rural credit contracts in the country, according to data from Bacen (2023). Within this scope, the work is divided into two parts: the first aims to understand the nuances and chronology of the spatial distribution of rural credit in the state of Rio Grande do Sul between 2013 and 2022, and the second part addresses the importance of rural credit for the development of productive activities and the integration of agronomic and technological management in rural properties in the state, from the perspective of rural producers. This provides a comprehensive view of the past, present, and future of rural credit for the rural producer in Rio Grande do Sul. In the first part, a chronological analysis of rural credit resource applications was conducted, followed by a descriptive analysis to introduce the topic and demonstrate the relevance of the main regions of the state. Subsequently, an analysis of the productive profile was carried out using the Normalized Rural Credit Index (INCR), which allows observation of whether a municipality's productive profile is more agricultural or livestock-oriented. Additionally, to verify the representativeness of a specific activity in a municipality, the Hirschman-Herfindahl Index (HHI) was applied. These data were made available using Geographic Information System (GIS) techniques, allowing for the description of the spatial distribution of rural credit through maps. Thus, the analysis model made it possible to identify the predominant agricultural activity in each municipality of the state and the changes that occurred over the analyzed period. This demonstrated that the state has a dynamic, multifaceted, and constantly evolving agricultural sector, as municipalities have modified their credit needs and adjusted their productive activities over the years. In the second part, which aims to analyze and understand the views and demands of rural producers in Rio Grande do Sul on the interaction between the rural credit model and agronomic management on their properties, a questionnaire was conducted, collecting the opinions of 240 rural producers in 88 different municipalities in the state on this topic. To understand the producers' perspectives, the responses were subjected to descriptive, factorial, and cluster analysis. Through these analyses, it was possible to examine the relationships of the respondents with the study variables, identifying the underlying structures inherent in the dataset. As a result, it was identified that producers wish to produce more efficiently and sustainably but face difficulties in obtaining resources through rural credit. This is because the current model fails to meet their needs, requiring updates to the credit line structures to address issues beyond mere food production, considering the entire property ecosystem. Thus, it was possible to obtain a comprehensive perspective on rural credit in Rio Grande do Sul, addressing its past and present as well as its future perspectives from the viewpoint of rural producers.